Cross-country skiing as a model of human movement analysis - Herzog, W. (Science and Skiing VIII. Book of the 8th International Congress on Science and Skiing, 2020)
Sport biomechanics is typically done for the following reasons: (i) understanding the sport and its mechanical demands; (ii) improving the performance of athletes by optimizing sport specific techniques; (iii) gaining insights into mechanisms of sportspecific injuries; and (iv) improving our understanding of basic human movement mechanics and control. In this short summary of our research on cross-country skiing, I will focus on the latest aspect: using sport (in this case cross-country skiing) to gain insights into some fundamental questions of human movement. These questions are centred on (i) Gait transitions (ii) The cost o f frequency of movement, and (iii) The mechanics and efficiency o f entrained breathing